PEMANFAATAN E-LEARNING SEBAGAI MEDIA EVALUASI PEMBELAJARAN BAHASA ARAB DI MADRASAH - Aryadin Saputra; Suparmanto, suparmanto; Nailal Hakika, Binti; Febrianti, Nia; Manan, M. Parihin (Program Studi Pendidikan Bahasa Arab (PBA), Universitas Islam Negeri Datokarama Palu, 2024)
Distance learning or what we usually know as e-learning. E-learning is a learning process using computer technology and computer networks or what we commonly know as the internet. E-learning is used by students to learn through computers. As we know, electronic-based learning is a new technique in terms of the teaching and learning process. This study aims to describe the use of e-learning-based learning media using the kahoot platform in Arabic language learning in class XI.A MA Assulami, Langko, Lingsar. This application works by means of game-based learning or can be called by. The intention is to involve more active participation between students and educators through ongoing learning competitions. The data collection technique used is observation by teaching students in the school. With this platform, learning becomes more interactive which will make teaching and learning activities more fun and certainly will not make the classroom atmosphere saturated when the teaching and learning process takes place.